DAMPAK PRAKTIK IJARAH TERHADAP PENDAPATAN PETANI DI DESA DAYAH MEURIYA KECAMATAN SYAMTALIRA ARON KABUPATEN ACEH UTARA - Mukhlish Muhammad Nur; Munardi Munardi; Ichsan Ichsan; Nazli Hasan; Rayyan Firdaus; Rifqi Arrazaq (LPPM, 2022)
This study examined the effect of the principle of Ijarah on farmers' income (a case study at Dayah Meuria Village, Syamtalyra Aron subdistrict, North Aceh Regency). This study used primary data obtained by distributing questionnaires to 85 respondents using nonprobability sampling. The data analysis method used was PLS with the help of the SmartPLS (Partial Least Square) application program.. The results indicated that the principle of Ijarah significantly affected farmers' income at Dayah Meuria Village, Syamtalyra Aron subdistrict, North Aceh Regency.